Dynamics of caste and law : Dalits, oppression and constitutional democracy in India - Berg, Dag-Erik (Cambridge Cambridge University Press, 2020)
"This book breaks new ground in the discussion of the relation between caste and law in India, representing a critical dimension in the postcolonial state. Today, caste has become a very visible phenomenon often associated with politics, social inequality and discrimination. India's constitutional democracy has been remarkable for its goal of creating equality in a context of caste. Despite constitutional promises with equal opportunities for the lower castes and outlawing of untouchability at the time of Independence, reoccurring atrocities and inadequate implementation of law have called for rethinking and legal change. This book develops an interdisciplinary approach to analyse how caste and law relate over time. Building on a postfoundational approach to critical explanation, it provides a new account of how Dalit experiences represent a starting point to analyse dynamics of law and caste-based domination. New concepts are used to interpret a comprehensive case study material. Making a clear departure from conventional disciplinary approaches, the book explains how caste-based oppression, public policy and the ontology of caste intersect. Sociological terms invented by Bhimrao Ambedkar, an anti-caste leader of Dalits and a scholar, are incorporated to explain the enduring relevance of caste. In addition to case studies of Dalit movements, atrocities and caste politics, it is argued through detailed examination of court cases that law could be re-directed to suit the members of dominant castes. The book will be of interest to students of South Asia and has comparative relevance for discussions of democracy, law and racism"--
Includes bibliographical references and index.
Keywords: Caste; Dalits; Dalits; Constitutional law; Democracy